The Effect of Some Spices of Plant Growth Promoting Rhizobacteria (PGPR) on Disease Severity and Reduction of Virus Infection of Cucumber mosaic virus (CMV) on Tomato Plant under Greenhouse Conditions (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
This research aimed to study the effect of three species of bacteria Azotobacter chroococcum, Bacillus megaterium and Frateuria aurantia with three inoculation manner (seeds, shoots and seed,  shoots) on suppressed the effect of Cucumber mosaic virus on tomato plants (pots),  by measuring the disease severity and reduction of virus infection. The experiment carried out in a greenhouse in Tartus in 2016. The results showed, that treatment with bacteria in single or mixed causing to reduction of disease severity and increase reduction of virus infection. In addition, the effect of bacteria was different according to the manner inoculation and the date of readings. The highest reduction of disease severity was observed in treatings A+B+F+CMVs+sh (after 14 and 28 days) 5%, 8.33% respectively. Consequently, the largest reduction of virus infection was viewed in A+B+F+CMVs+sh (after 14 and 28 days) %54.54, %54.54, respectively compared with the control was 0%. تأثير بعض أنواع بكتريا الرايزوسفير في الشدة الإمراضية ونسبة الإصابة بفيروس موزاييك الخيار على نبات البندورة في ظروف الزراعة المحمية هدف البحث لدراسة تأثير استخدام ثلاثة أنواع من بكتريا Azotobacter chroococcum , Bacillus megaterium و Frateuria aurantia بثلاث طرائق مختلفة (تلقيح بذور, تلقيح شتول, تلقيح بذور وشتول) في الحد من تأثير الإصابة بفيروس موزاييك الخيار Cucumber mosaic virus (CMV) على نباتات البندورة المزروعة في أصص عن طريق تقدير الشدة الإمراضية ونسبة تخفيض الإصابة الفيروسية. نفذ البحث في موسم 2016 ضمن نفق بلاستيكي في محافظة طرطوس. أظهرت النتائج أن المعاملة بالبكتريا بشكل مفرد أو مختلط أدت إلى انخفاض الشدة الإمراضية وزيادة نسبة تخفيض الإصابة بفيروس موزاييك الخيار، كما اختلف تأثير التلقيح بأنواع البكتريا المدروسة حسب طريقة المعاملة وتاريخ أخذ القراءات وكان أكبر تخفيض للشدة الإمراضية للفيروس هي لمعاملة تلقيح بذور وشتول البندورة بالأنواع البكتيرية الثلاثة معاً، إذ بلغت (بعد 14 و28 يوماً من العدوى الفيروسية) 5, 8.33% على التوالي, بالمقارنة مع الشاهد 48.33 و61.66 %على التوالي. كما كان أكبر تخفيض لنسبة الإصابة هو للمعاملة السابقة إذ بلغت بعد 14 و 28 يوماً من العدوى الفيروسية %54.54, %54.54 على التوالي بالمقارنة مع الشاهد 0%.